PREDIKSI FRAGMENTASI HASIL PELEDAKAN MENGGUNAKAN MODEL ROCK ENGINEERING SYSTEM (RES) DI PT BHUMI RANTAU ENERGI KABUPATEN TAPIN PROVINSI KALIMANTAN SELATAN - RAHUL GONZALES; DEDI YULHENDRA (Departemen Teknik Pertambangan FT UNP, 2023)
Blasting is the process of breaking up rock (overburden) using explosives. The size of the blasted rock is called fragmentation. The size of the blasted rock fragmentation has an important influence on the next process (excavation and transport). Blasting at PT Bhumi Rantau Energi (BRE) produced 30.925% boulders so that the digging time required was 12.33 seconds which resulted in a digging rate of only 510 BCM/hour. This is still far from PT BRE's target of boulder size <20%, digging time of 11 seconds and digging rate of 550 BCM/hour. Therefore, a method is needed to predict the fragmentation size resulting from the blasting geometry and site conditions. The Kuz-ram method is a commonly used method to predict fragmentation size, but it only considers a few factors of rock fragmentation formation. The Rock Engineering System (RES) model has more parameters to predict fragmentation size than the Kuz-ram method. Therefore, the RES model with 14 parameter* was used in this study to predict the fragmentation size of blasted rock. The analysis results stated that the RES model has an R2 value of 0.43, which means that there is a moderate relationship between the actual fragmentation and the prediction of the RES model. In addition, the evaluation result found that this model only has an RMSE value of 9.37, which means that the probability of error is small, making it suitable for predicting the fragmentation size.Keyword: Blasting, Fragmentation, Rock Engineering System